Level maternal and child health and family planning - Gonzáles Enders, Rodolfo (2015)
To discuss the issue have proposed we should review some important concepts about health and conditions of it that are applicable to maternal and child health in order to establish the relationship between her and family planning, as a preventive factors that will allow maintain the highest standards of individual and collective health. There is a definition of health which is issued by the WHO, which is considered utopian, but we must admit that it involves all the factors that will affect the level of health and therefore is quite real, the difficulty of understanding it is that we define health through negative indicators such as for example the morbidity and mortality, whereas this definition presents to health in a positive way, as a state of complete physical, mental and social well-being. This confuses us as we are unable to measure it in those terms. But when we think deeply, especially when we take preventive action this statement is the theoretical framework, most important reference that we must continue to perform efficiently and effectively health actions.